THE EFFECT OF INVESTMENT UNDERSTANDING, MINIMUM INVESTMENT CAPITAL, MOTIVATION AND RISK PERCEPTION ON INVESTMENT INTEREST - Pratista Ramadhani, Anggi; Jasman, Jumawan; Sahrir, Sahrir (JURNAL EKBIS, 2025)
This study aims to analyze the influence of investment understanding, minimum investment capital, motivation, and risk perception on the investment interest of the millennial generation in the capital market. This study uses a quantitative approach with a cross-sectional design. The research sample was 97 respondents from the millennial generation in Palopo City, who were selected using a purposive sampling technique. Data collection was carried out by distributing questionnaires with a Likert scale, while data analysis used multiple linear regression with the help of SPSS software. The results of the study showed that partially, investment understanding, minimum investment capital, motivation, and risk perception had a positive and significant effect on investment interest. Simultaneously, the four independent variables contributed significantly to investment interest with an influence level of 66%. This shows that the millennial generation tends to be interested in investing if they have a good understanding of investment, affordable initial capital, high motivation, and well-managed risk perception.